2009
DOI: 10.1136/jcp.2009.066100
|View full text |Cite
|
Sign up to set email alerts
|

Multiple squamous hyperplastic-fibrous inflammatory polyps of the oesophagus: a new feature of eosinophilic oesophagitis?

Abstract: This report describes the unusual case of a 12-year-old boy with multiple polyps in the oesophagus and concurrent eosinophilic oesophagitis (EoE). Polyps were of a fibrous-inflammatory composition featuring eosinophils, mast cells, hyperplastic epithelium and fibrosis, which are all features described with EoE. EoE is an increasingly recognised clinicopathological disorder characterised by large numbers of eosinophils infiltrating the oesophageal mucosa. Polyps in the oesophagus are rare, have not previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Reflux esophagitis is only one cause of esophagitis, and there are other postulated triggers of esophageal polyps. Despite recent case reports, none of our patients had endoscopic‐histologic evidence of eosinophilic esophagitis, and esophagitis did not consistently relate to any particular histologic subtype.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Reflux esophagitis is only one cause of esophagitis, and there are other postulated triggers of esophageal polyps. Despite recent case reports, none of our patients had endoscopic‐histologic evidence of eosinophilic esophagitis, and esophagitis did not consistently relate to any particular histologic subtype.…”
Section: Discussioncontrasting
confidence: 88%
“…Resolution of polyps has also been reported with antireflux therapy. 24 Medications, infections and recurrent vomiting 1 are other potential etiologies, while underlying neurofibromatosis, 9,13 Crohn's disease, 25,26 eosinophilic esophagitis 27,28 and Barrett's esophagus 1,29 have also been reported in adults.…”
Section: Introductionmentioning
confidence: 99%
“…EREFS has been validated in studies performed in Western countries, and shown to have usefulness for diagnosis as well as monitoring treatment response in patients with EoE 19 22 23 . In addition, several minor endoscopic findings have been reported, such as esophageal polyps 24 25 26 and cobblestone-like appearance 27 . ABS also features nodular formation, though the linear arrangement occurs at uniform intervals and is completely different from those previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…They are most common around the gastro-oesophageal junction and distal oesophagus and are associated with gastro-oesophageal reflux disease in most cases. They may also be seen with injury due to medication, infection, anastomotic or polypectomy sites, vomiting, photodynamic therapy and eosinophilic oesophagitis [1][2][3][4].…”
Section: Inflammatory/hyperplastic Polypmentioning
confidence: 99%